PEMETAAN ZONA RAWAN BENCANA BANJIR BERBASIS PARTISIPATIF DI KECAMATAN GONDANGLEGI KABUPATEN MALANG - Ferdiannanda, Alfitka Septa; Putra, Dwi Fauzia; Kurniawati, Dwi (Social Landscape Journal, 2024)
The Gondanglegi Subdistrict is one of the areas prone to flooding due to high-intensity rainfall and a predominantly low-lying topography. One effort in flood disaster mitigation is through the implementation of participatory mapping involving active participation from various stakeholders, including local communities, local governments, and non-governmental organizations. The objectives of this research are to conduct participatory mapping regarding the vulnerability level of flood disasters in the Gondanglegi Subdistrict of Malang Regency, to understand the role of participatory mapping in flood disaster mitigation planning in the Gondanglegi Subdistrict of Malang Regency, and to identify the factors causing floods in the Gondanglegi Subdistrict of Malang Regency. This research adopts the Participatory Rural Appraisal (PRA) approach as the main method. The results of this research indicate four levels of flood disaster vulnerability in the Gondanglegi Subdistrict, namely not vulnerable, moderately vulnerable, vulnerable, and highly vulnerable. Participatory mapping provides significant benefits to the community in terms of understanding and mitigating floods. Floods are caused by natural factors such as rainfall and topography, as well as non-natural factors such as inadequate water channels and indiscriminate waste disposal by the community.